PENGARUH PENGGUNAAN MEDIA SOSIAL DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 40 JAKARTA - Relwandani; Eryanto, Henry; Wolor, Christian Wiradendi (Transpublika Publisher, 2023)
This study aims to determine how the influence of Social Media Use and motivation on entrepreneurial interest at SMK Negeri 40 Jakarta. The method used in this research is a survey with a quantitative approach. The population in this study involved students of SMK Negeri 40 Jakarta, totaling 198 students. The sample was taken using proportionate stratified sampling technique with the Slovin formula with a sample size of 132 students and an accuracy of difficulty level of 5%. For data analysis techniques using SmartPLS 4.0 software and then analyzing several calculations consisting of measurement model analysis, structural model analysis, and direct effect hypothesis testing. The results of this study found that the variable X1 on Y using the calculation of t-statistics amounted to 4,511> 1.96, and the calculation value of the p-value was 0.000 <0.05; then for X2 on Y using the calculation of t-statistics amounted to 4,837> 1.96, and the calculation value of the p-value was 0.000 <0.05. The results of the calculation using F-Square on variable X1 on Y have a value of 0.147. Meanwhile, with the same calculation, the X2 variable on Y has a value of 0.239. The conclusion of this study is that the use of social media and motivation towards entrepreneurial interest together and directly have a positive and significant influence on students at SMK Negeri 40 Jakarta.